Building Information Modelling (BIM)—versioning for collaborative design - Zada, A. Jaly; Tizani, W.; Oti, A.H. (2014)
The engineering design process is a complicated activity. It is often characterized by multi-disciplinary teams in multiple places working together on a single project, using different models and software tools. In addition, such activities generate a large amount of data that require exchange among designers and stages of the work. In industry, the current collaboration approaches often focus on integrating and managing multiple models from multi-designers. Building Information Modelling (BIM) is playing a major role in facilitating collaboration. BIM provides an opportunity to electronically model and manage the vast amount of information embedded in a building project, from conception to completion. In the building design process, changes and modifications are inevitable even in the contemporary BIM approach. Such changes need to be well managed to keep track of changes to ensure that designers have an up-to-date version of the BIM model. The main goal of this research is to develop a collaborative BIM platform that tackles the challenges of integrating object versioning, as a change management approach, and an IFC model, as data representation of BIM. This has been done through suggesting new IFC extensions to add further concepts representing the history of changing to any object of the model. It also explores possibilities of adding or merging object-based change information to existing BIM models to enable the representation of design intentions, identification of affected changes numerically and visually. A prototype system is implemented in C#, using .NET framework and Revit API platform. This paper concludes that the proposed system can contribute to improving collaboration - in terms of tracking and management of affected changes during multi-disciplinary design process.